2021
DOI: 10.3389/fmars.2021.705332
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Alterations of the Distal Intestinal Microbiota, Transcriptome, and Metabolome of Hybrid Grouper by β -Conglycinin With Reconciliations by Sodium Butyrate in Feed

Abstract: Different doses of β-conglycinin produce different regulations on the intestinal health of aquatic animals, affecting the absorption of nutrients, indirectly changing water quality. Sodium butyrate (NaB) can effectively alleviate the negative effects caused by high-dose β-conglycinin. We investigated the positive response to low-dose (1.5%, bL) and negative response to high-dose (6.0%, bH) β-conglycinin and supplementation with NaB (6.0% β-conglycinin + 0.13% NaB, bHNaB) in terms of water pollutants, microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…The linoleic acid metabolism, glycosaminoglycan degradation, and oxidative phosphorylation pathway were considerably enriched in the TB group than in the control. Enhancement of the linoleic acid metabolism pathway facilitates the promotion of lipid utilization in A. japonicus [55]. Reports suggested an important role for the glycosaminoglycan degradation pathway in the modulation of growth factor signaling [50].…”
Section: Discussionmentioning
confidence: 99%
“…The linoleic acid metabolism, glycosaminoglycan degradation, and oxidative phosphorylation pathway were considerably enriched in the TB group than in the control. Enhancement of the linoleic acid metabolism pathway facilitates the promotion of lipid utilization in A. japonicus [55]. Reports suggested an important role for the glycosaminoglycan degradation pathway in the modulation of growth factor signaling [50].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal microbiota are involved in the regulation of host energy-uptake efficiency, which was significantly associated with weight gain ( Looft et al, 2014 ; Kim et al, 2015 ) and FE ( Singh et al, 2012 ; Mccormack et al, 2017 ) and plays an important role in maintaining the stability of the intestinal environment ( Chung and Kasper, 2010 ). Changes in intestinal microbiota could inevitably influence intestinal metabolic function and further affect the physiology of organisms ( Levy et al, 2017 ), which can be partially indicated by intestinal metabolites ( Yin et al, 2021 ). Therefore, numerous studies have analyzed intestinal microbiota structure and metabolites to explore the regulatory mechanisms of FE ( Metzler-Zebeli et al, 2019 ; Gardiner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%